Multi-objective routing aware of mixed IoT traffic for low-cost wireless Backhauls - Medeiros, Vinícius N.; Silvestre, Bruno; Borges, Vinicius C. M. (Journal of internet services and applications, 2019)
The futuristic wireless networks expects to provide adequate support for distinct kind of applications, their diverse requirements, and scenarios for future Internet systems, such as Internet of Things based on multimedia and sensor data, while figuring out low cost solutions to offload the mobile communication core. In this context, Low-cost Wireless Backhauls (LWBs) can be useful, since they are based on cheap WLAN technologies, such as Wireless Mesh Networks that provide capacity for future IoT applications based on mixed traffic. The routing is a fundamental process to provide communication in these multi-hop networks and multi-objective routing optimization algorithms based on Integer Linear Programming (ILP) models have been studied in the literature to address this problem, but there is a lack of solutions for mixed traffic. For this reason, we propose a novel ILP multi-objective approach, called Multi-objective routing Aware of miXed traffIc (MAXI), which employs three weighted objectives to guide the routing in WMNs with different applications and requirements. In addition, we provide a comparative analysis with other relevant approaches of routing using NS-3 to evaluation based on simulation, that takes into account different types and levels of interference (e.g. co-channel interference and external interference) focused on mixed IoT traffic for elderly healthcare scenario. Finally, we demonstrate the effectiveness of the proposed approach to support the requirements of each application through the appropriate combination of objective functions, mainly in dense scenarios with high level of interference.